The Jewish messiahs : from the Galilee to Crown Heights - Lenowitz, Harris (Oxford University Press, 1998)
In this book, Harris Lenowitz explores the fascinating history of Jewish messianic movements. Looking in detail at all of the Jewish messiahs about whom anything is known, he introduces each of these figures in turn, and offers extensive excerpts of the original texts that tell their stories. The messiahs whom we meet in these pages range from the inspiring to the tragic and bizarre. By examining the messianic idea in the tradition which gave birth to it, Lenowitz both sheds new light on this engrossing aspect of Jewish history and provides a firmer basis for understanding contemporary messianic groups.